If for any reason [large type] - Walsh, Courtney, 1975- (Center Point Large Print, 2020)
"A woman, guided by a book of letters left behind after her mother died, inherits her childhood summer cottage on the island of Nantucket. She has one goal--to renovate it, sell it, and get on with her life; but a chance meeting with the boy next door leads her down a path of discovering her purpose, piecing together what really happened to her mother the night she died, and the realization that maybe her mother's letters weren't the source of wisdom she thought they were. Can the words in those old letters help her heal or will they only keep her separated from the people and the place that might bring her what she wants most of all--a family of her own?"--